(untitled) (Research, Society and Development, 2022)
The sequelae of COVID-19 have a real impact on the quality of life of people who come into contact with the SARS-CoV-2 virus, and may persist indefinitely. Objective: Unveil the perception of what is experienced by people with sequelae of COVID-19. Methods: Qualitative study with a phenomenological approach according to Merleau-Ponty, carried out with 14 people diagnosed with sequelae of COVID-19 and who were undergoing treatment during the period of the phenomenological interviews, from February to May 2021. The interview was guided by the triggering question: "Tell me what your perception of your lived with COVID-19 sequels is, how it affected your mind and body." Results: This is an excerpt from the Master’s thesis in Nursing entitled "The perception of what is experienced by people with sequelae of COVID-19", approved by CEP/UFAL, CAAE no. 41216620.6.0000.5013. The results showed four ontological units that were analyzed and interpreted in the light of the theoretical-philosophical framework of Maurice Merleau-Ponty. Among the categories that emerged from the testimonies, the ontological unit “Perceiving your sick body and living in the world-of-COVID-19” (body) is presented. Conclusion: I could see that the being-sequenced by COVID-19 has a body with limitations that has its world abruptly changed, having its ways of relating through the senses impacted (loss of smell/taste); composed of a mind that no longer remembers the day that he was not afraid, insecure, feared for his life and those he loves. It is hoped that this study can contribute to the implementation of initiatives that are capable of offering humanized care.